2015
DOI: 10.1186/s13287-015-0194-y
|View full text |Cite
|
Sign up to set email alerts
|

Differential ability of MSCs isolated from placenta and cord as feeders for supporting ex vivo expansion of umbilical cord blood derived CD34+ cells

Abstract: IntroductionEx vivo expansion of umbilical cord blood (UCB) is attempted to increase cell numbers to overcome the limitation of cell dose. Presently, suspension cultures or feeder mediated co-cultures are performed for expansion of hematopoietic stem cells (HSCs). Mesenchymal stem cells (MSCs) have proved to be efficient feeders for the maintenance of HSCs. Here, we have established MSCs-HSCs co-culture system with MSCs isolated from less invasive and ethically acceptable sources like umbilical cord tissue (C-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
57
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 45 publications
(61 citation statements)
references
References 37 publications
4
57
0
Order By: Relevance
“…According to our earlier findings [22], we observed that P-MSCs-CM had superior cryoprotective activity than C-MSCs-CM. This difference may be attributed to the distinct secretory profiles exhibited by C and P-MSCs as described in this report [22].…”
Section: Discussionsupporting
confidence: 65%
See 2 more Smart Citations
“…According to our earlier findings [22], we observed that P-MSCs-CM had superior cryoprotective activity than C-MSCs-CM. This difference may be attributed to the distinct secretory profiles exhibited by C and P-MSCs as described in this report [22].…”
Section: Discussionsupporting
confidence: 65%
“…This difference may be attributed to the distinct secretory profiles exhibited by C and P-MSCs as described in this report [22]. Although, P and C-MSCs are in close anatomical proximity, both exhibited differences in their characteristics, such as higher concentration of HGF in P-MSCs- CM compared to C-MSCs-CM [22]. HGF is known to have anti-oxidant effect [20,21] which might have contributed to the superior cryoprotection provided by the P-MSCs-CM.…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…Thus, we transplanted the stem cells combined with placentapooled cytokines. Placenta-derived mesenchymal and hematopoietic stem cells as well as cytokines are homologous (Kadekar et al 2015), and the cytokines combined with DMEM/F-12 can maintain the survival of the mesenchymal and hematopoietic stem cells.…”
Section: Discussionmentioning
confidence: 99%
“…Marrow stromal cells, firstly being identified in bone, can differentiate into multiple lineages, such as osteoblasts, adipocyte, chondrocytes, and myoblasts in vitro . With the stemness of self‐renewal and multipotential differentiation ability, MSCs from other various tissues are more and more recognized as seed cells for bone remodeling . Due to the features of expansion and multiple differentiation potential in vitro, MSCs are supposed to be a core of the tissue bone engineering …”
Section: Introductionmentioning
confidence: 99%